Bus Stations Categorisation Criteria - Štefančić, Gordana (Promet - Traffic&Transportation, 2012)
In order to establish the respective criteria for categorisationof bus stations, since no criteria have been determined yetbased on the world experience, the existing conditions havebeen analysed in all 64 bus stations in Croatia by use of questionnaires.Based upon the basic and additional facilities, busstations fall into four categories: A, B, C and D, and these arethen called basic and additional criteria.The basic criteria involve specific aspects obligatory forevery category. The number and type of aspects refer at thesame time to the minimum number of points assigned per category.There exists a 3-point discriminating difference betweenindividual categories.The additional criteria involve the accompanying aspectsrequired for the functioning of the system; they are optionalwithin the frame of a given number of points per category, andthere exists a 4-point dicriminating difference between individualcategories.Categorisation makes the basis for establishing the pricelist at bus stations, in turn imposing the requirement of provisionof a given level of bus stations services.